Characteristics of Posttraumatic Nightmares and Their Relationship to PTSD Severity Among Combat Veterans With PTSD and Hazardous Alcohol Use. Issue 3 (March 2022) - Possemato, Kyle; Silander, Nina; Bellete, Nardos; Emery, J. Bronte; De Stefano, Leigha; Pigeon, Wilfred
Abstract: Although nightmares are known to predict the clinical course of posttraumatic stress disorder (PTSD), research on the relationship between specific nightmare characteristics and PTSD severity is sparse. This study conducted a secondary analysis to explore how five nightmare characteristics are cross-sectionally related to PTSD severity in 76 combat veterans with PTSD and at-risk alcohol use. Consistent with emotional processing theory, we hypothesized that more replicative, threatening, realistic, and easily recalled nightmares would be associated with more severe PTSD, whereas those with greater symbolism would predict lower PTSD severity. Nightmares narratives were audio-recorded and rated by multiple coders. Multiple analyses of variance explored the relationship between nightmare characteristics and PTSD clinical indicators. Most nightmares were realistic, easily recalled, and involved significant threat. Greater realism and replication were associated with greater PTSD severity. Realistic and replicative nightmares may be markers of more severe PTSD and may indicate that less emotional processing of the trauma has occurred.